Parafrasa Lirik Lagu Bertema Pelacur Karya Iwan Fals - Hermintoyo, Muhamad (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2022)
Song lyrics, just like poetry has a physical element and an inner element. In the hands of creative authors will look aesthetically pleasing by utilizing diction, rhymes, imagery and rhetorical means. The exact diction of the ability to capture the senses provides imagery, and setting on the lyrics he makes. Lyrics are generated from real life, squeally in the form of imagined imitations of life. The theme of nightlife is directly related to the perpetrators, such as prostitutes/ prostitutes/ prostitutes/ night butterflies/ tunasusila/ pramunikmat and other terms; bromocorah/ criminal/ residivis; striped nose guest and so on. Iwan Fals as a lyricist and songwriter was able to photograph the social life of the night world. The lyrics of the song